Methodological Nature and Epistemological Bases of Qualitative Studies in Marketing (Global Journal of Management and Business Research, 2023)
This research portrays the epistemological bases on which qualitative studies in marketing are based. In the meantime, the main objective was to analyze how qualitative research published in the Revista Brasileira de Marketing is constructed, based on conventional and unconventional epistemologies. The methodological design was that of documentary research with content analysis. The under-standing and interpretation of the articles, as well as the critical evaluation carried out, allow inferring that qualitative studies in marketing have a strong emphasis on the conventional basis and have positivism and the empiricist-systemicfunctionalist approach as their central assumption. Furthermore, the influence of unconventional epistemological bases, in two articles, signals the emergence of critically oriented studies. Even so, they are approximations, flirtations, rather than critical studies per se, because they do not widely appropriate the general categories that characterize, guide and found the critical theoretical-methodological scheme.
Keywords: epistemology; qualitative research; marketing; epistemology in marketing